Impacto del manejo de agroquímicos, parte alta de la microcuenca Chorro Hondo, Marinilla, 2011 (2013)
ABSTRACT: To determine the impact generated by the use of agrochemicals in the upper area of the Chorro Hondo micro watershed in the municipality of Marinilla (Colombia)in order to develop measures contributing to environmental and quality of life improvement. Methodology: a cross sectional,descriptive study with a univariate and bivariate analysis of the surveys answered by 6 suppliers and 35 farmers who were located in their respective agricultural lands. Additionally, the study included direct observations of the properties located within the first 2000 meters of the micro watershed. Likewise, water, soil and air samples were analyzed in search of Chlorothalonil and Mancozeb, the most common active ingredients of the agrochemicals used in this area. Results: in all of the 35 properties, 86% of the farmers performed some kind of agricultural activity and 74% used agrochemicals.Similarly, 58% of the farmers knew the risks associated with the use of these products, intoxication being the most common(occurring in 47% of the individuals). Moreover, 42% did not use a special suit and 31% felt that the water was contaminated with agrochemicals. The concentration of the active ingredients in the water, air and soil was below the detection limit of the methods. Discussion: Marinilla has a complex set of problems regarding agrochemical handling; Chlorothalonil is carcinogenic, and the sale license for Mancozeb has been canceled; the farmers do not meet the basic requirements for: agrochemical storage, transportation and waste disposal; finally,the farmer do not usethe appropriate personal protectiongear.